ANALISIS PENGARUH PROFITABILITAS DAN STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN BUMS YANG TERDAFTAR DI BURSA EFEK INDONESIA - Niken Ayuningrum (Politeknik Sekayu, 2016)
This study examine the effect of profitability and institutional owner on profitability variable at the private companies listed on Indonesian Stock Exchange in 2009-2013. The purpose of this study to determine the effect of variables ROAand institutional owneron PBV at the private companies.The population in this study was 392 companies, that sample are taken by purposive sampling method with the specified criteria were 30 companies. The analysis technique used multiple regression and performed classical assumption in advance. The results of this study show that, 1) ROA was positive and gave significant effect on the PBV, 2) Institutional owner was positive and gave significant effect on the PBV, then 3) ROA and institutional owner was positive and gave significant effect on the PBV at the private companies.